Vulvar Diseases that Required a Biopsy: A Retrospective Study - Bouceiro-Mendes, Rita (2021)
Introduction: The vulvar area may be affected by many noninfectious conditions with similar clinical appearance, requiring a cutaneous biopsy. Our goal was to characterize the noninfectious vulvar diseases that required a biopsy in a southwestern Europe Central Hospital during a 10-year period. Methods: A retrospective study of all the noninfectious vulvar diseases with histological confirmation diagnosed in our institution was conducted between January 1, 2008 and December 31, 2017. Results: The sample included a total of 323 biopsies from 317 patients, aged between 11 and 98 years (mean age of 54.2 years). A total of 36 vulvar diseases was identified. Neoplastic conditions were the most frequently found, particularly melanotic macules (22.3%). The most frequent malignant tumor was vulvar intraepithelial neoplasia (6.2%) and squamous cell carcinoma (5.6%). The most common dermatosis was lichen sclerosus (12.7%). Conclusion: Neoplasms were the most frequently diagnosed conditions affecting the vulvar area that required a biopsy. Ruling out malignancy was also the main reason to perform a biopsy. This study highlights the variety of noninfectious diseases that may affect the vulva and require a biopsy. Since vulvar diseases may be serious and carry high levels of patient distress a correct understanding of these conditions is crucial.